Some studies on haemonchiosis in sheep and goats in New Valley Governor ate. Egypt. - Osman, Fathy Ahmad (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
Haemonchuosis is a serious health problem which causes lower production host and hazard economic effect due to high morbidity, mortality, cost of treatment and control measures . The paper carried to study the prevalence of haemonchus species parasite infection a mange sheep and goats in New-Valley Governorate .Egypt, beside evaluated the efficiency of different diagnostic methods (Postmortem examination, fecal examination and ELISA technique) and determined the relationship between some hematological and biochemical parameters with the disease. Study were carried on total of 530, (225 sheep and 305 goats) and 100 clinically and laboratory healthy animals (50 sheep and 50 goats), as a control animals, from May 2014to May 2015. Adult worm was collected by opening the abomasum’s in slaughterhouse in normal saline for Preparation of crude somatic antigen. Two blood sample collected randomly from each animal admitted to slaughterhouse and control animal for evaluated of hemato-biochemical parameters and ELIZA test study .Fecal sample collected randomly from each sheep and/or goats admitted for slaughter and control animal for fecal examination. ELIZA technique was carried with the preparation of crud somatic antigen, hematological and biochemical analysis was carried on to comparisons the parameters changes in the diseased and healthy sheep and goats. The study revealed that, 82(15.47%),75(14.15%) ,71(13.39) out of 530 of sheep and goats were found to be positive by ELISA, postmortem and fecal examination respectively, where the sensitivity of ELISA assay was 98.97%, while specificity was 98.24% in compared with postmortem examination and 96.47% ,96.96% ,respectively, in compared with fecal examination. A range of hemato-biochemical measures were revealed significantly different between infected groups and controls group, where the serum packed cells volume (PCV),Erythrocyte sedimentation rate (ESR), hemoglobin and total RBCs were significantly decreased (P<0.05), while the concentration of eosinophil, Lymphocytes were significantly increased (P<0.05) . The hematological studies indicated that, The percentage of neutrophils was low while lymphocytes count, number of basophiles and monocytes number in percentage were high, while biochemical studies revealed that, total serum proteins, Albumin/ Globulin Ratio (A/G Ratio) were significantly decreased (P<0.05) in infected animals . Conclusion; ELIZA test is more efficacy and reliable test in diagnosis of haemonchus parasite infection in sheep and goats because the test can detect the infection with the pre-patent stat and before the parasite attain to sexual maturity. Also the change in hemoglobin concentration, total serum proteins, total RBCs and A/G ratio were important indicators of haemonchuosis diagnosis and control in sheep and goats.